PENINGKATAN KEMAMPUAN MENGHAFAL ASMAUL HUSNA MELALUI METODE BERNYANYI PADA SISWA - Amir Mukminin; Fadhillah Hayya, Annisa; Mustofa, Zamzam (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2024)
This research aims to determine efforts to improve the quality of memorizing Asmaul Husna by using the singing method. The research method uses Classroom Action Research (PTK) with 2 cycles with four component stages, namely: 1) Planning, 2) Implementation (acting), 3) Observation (observing), and 4) Reflection (reflecting). The results of this research show that from the first cycle to the next cycle there has been an increase. It becomes easier for students to memorize Asmaul Husna. The student learning results show that the application of the singing method has a positive impact on memorizing Asmaul Husna in class 1 students at Kedungjati State Elementary School. The singing method can improve student achievement because they are active, creative and feel happy during learning. The results of the research showed that the students' singing method succeeded in increasing their memorization of Asmaul Husna, shown in the pre-cycle by 33%, in the first cycle it was 58%, while in the second cycle it increased by 83%.